Association Between Endothelial Cell Stabilizing Medication and Small Vessel Disease Stroke: A Case-Control Study - Becker, Charlotte Elisabeth; Quinn, Terence J.; Williams, Anna (Frontiers in Neurology, 2019)
Increasing evidence suggests a role for endothelial cell (EC) dysfunction in pathogenesis of cerebral small vessel disease. Commonly used medications including certain antihypertensives and statins have EC-stabilizing effects. We used individual patient data from completed acute stroke trials to assess whether prior exposure to EC- stabilizing medications was associated with lacunar stroke, using lacunar stroke as a clinical proxy for cerebral small vessel disease. Across 12002 patients with relevant data, 2855 (24%) had a lacunar stroke presentation. Univariable analyses suggested potential confounding from vascular diseases treated with EC-stabilizing medications. Initial multivariable logistic regression gave conflicting results when describing the independent association of exposure to EC-stabilizing medication and lacunar stroke in the complete population (O.R. 0.87 95% C.I.:0.77-0.98) and limited to those taking any antihypertensive (O.R. 1.51 95% C.I.:1.21-1.88). Re-running the analyses including statins in the EC- stabilizing category suggested a beneficial effect of EC-stabilizing medication exposure on lacunar stroke incidence (O.R. 0.83 95% C.I.:0.73-0.93). These results align with recent pre-clinical data and would support interventional trials of EC- stabilizing medication for preventing cerebral small vessel disease. Our results also suggest that analyses of EC-stabilizing interventions need to adjust for potential endothelial effects of other co-prescribed medication.